Teachers’ Perspectives on Task-Based Language Teaching: A Case Study at International Islamic University Malaysia - Musazay, Asma; Khalid, Madihah (IIUM, 2017)
Abstract: The term task-based language teaching (TBLT) is widely used in the context of second language acquisition in terms of a curriculum which promotes actual language use. However, little research has been conducted in Malaysia regarding TBLT and its implicit method. This study, therefore, aims to explore and research the perceptions of CELPAD teachers towards TBLT, at the International Islamic University Malaysia (IIUM). The research aims to determine the level of awareness, understanding, and the perception that teachers have towards this method, as well as whether they employ it in their classrooms or not. The study employs a qualitative methodology, namely ‘case study’. The data collection instruments consist of interviewsof three randomlyselected instructors at CELPAD, one for each level ranging from level 4-6. The overall findings show that the CELPAD teachers possess a clear understanding of TBLT, agreeing that TBLT is beneficial. However, they are still unsure of the advantages of using it in the classroom. Furthermore, there is some measure of fear in adopting task-based language teaching fully primarily as a result of the problems they face pertaining to the end of semester assessment; the English Placement Test. As a result, it is found that some teachers use a mixed approach of both TBLT and traditional teacher-centered approach.